PENGEMBANGAN EVALUASI PEMBELAJARAN MENGGUNAKAN WORDWALL GAME SHOW QUIZ PADA MATERI BAGAIMANA BENTUK INDONESIAKU - Asysyifa, Anita Nur; Mulyawati, Yuli; Zen, Dendy Saeful (Akademika, 2025)
Abstract: Anita Nur Asysyifa (037120070) Development of learning evaluation using wordwall game show quiz on the material of how my Indonesia looks like. The evaluation tool used on the material of how my Indonesia looks like for grade V students is still not interesting. This study aims to develop and find out the feasibility of evaluation using the wordwall website how my Indonesia looks like. This study is a Research and Development (R&D) study with the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). This study involved three lecturers from Pakuan University as material experts, media experts, and language experts, as well as one teacher from SDN Cipaku Perumda as a material expert on how my Indonesia looks like. The material expert gave a validation score of 96% including the very feasible category, the media expert gave a score of 84% including the feasible category, and the language expert got a score of 100% with the very feasible category. The results of the pretest were 62% and the results of the posttest were 80.5 with the feasible category from the two tests conducted, getting an N-gain of 0.54 and can help students actively in conducting learning evaluations. It can be concluded that the development of learning evaluation using the wordwall website is suitable for use by teachers and grade V students.